"A Home for Poets": The Liberal Curriculum in Victorian Britain's Teachers' Training Colleges. Issue 1 (February 2014) - Bischof, Christopher Robert
Abstract : In the 1850s, at St. Mark's training college in Chelsea, London, ten students regularly violated the "lights out" rule in the evening at the end of long, exhausting days. Desirous of increasing their culture and general knowledge, they gave over half an hour every evening before sleep to what they styled, after the working-class clubs of the same name, "a mutual improvement society" in which they took turns giving lectures on a wide range of topics. They were not alone: throughout the second half of the nineteenth century, teachers-in-training across Britain supplemented their already daunting workload by writing poetry, reading novels, discussing Shakespeare, and holding debates about pressing social and political questions. From the perspective of many Victorian observers and historians today, this anecdote is an anomaly, an aberration that carries little weight in telling the story of the training colleges in which the majority of teachers in Victorian Britain eventually came to receive an education. For them, training colleges were the sites of rote memorization and pedagogical learning. Though some educationalists called for a more liberal curriculum for teachers, according to this view, teachers' education only began to emphasize expansive reading, original thinking, the cultivation of the individual, and general curiosity beginning in the 1890s with the rise of day training colleges affiliated with universities.